The Use of Audio Visual Media In Learning to Write Descrptive Texts for Students Of Class VII The Modern Islamic Boarding School Baharuddin Janji Mauli Muaratais, South Tapanuli Regency - Gustiar, Asrif; Angraini Lubis, Anita (Jurnal Hata Poda, 2025)
The Backgrounds of this research problem is students find it difficult to understand and write descriptive text due to a lack of ideas for describing something. In using audio-visual media in learning to write descriptive text, there are obstacles faced by teachers, namely limited technological capabilities and time utilization using audio-visual media. The use of audio- visual media in this modern era should be utilized more because it has been proven to improve student learning outcomes, this is proven by the results of observations and interviews with Indonesian language teachers at the Baharuddin Janji Mauli Muaratais Modern Islamic Boarding School. The use of audio-visual media aims to provide students with more understanding in writing descriptive texts through video and audio which can give students an idea of the object to be described. This research used a qualitative research methodology with Indonesian language teachers, school principals and class VII students at the Baharuddin Modern Islamic Boarding School as informants with a total of16 individuals. The results of the research showed that students were able to write descriptive texts well because they did not find it difficult to put words together and get ideas for writing so that after using audio-visual media, So it can be concluded that the use of audio visual media in learning to write descriptive text is effective.Keywords: Writing Descriptive Text; Audio Visual Media.